The Effect of Training With and Without Follow-up Through Telenursing on the Management of Stage 1 Hypertension in Older People - Maryam Moghadas; Ali Mohammadpour; Reza Ghasemi; Hosein Ajamzibad (Iran University of Medical Sciences, 2024)
Background: Hypertension is a risk factor for heart and blood vessel diseases, so it is crucial to teach patients how to control their hypertension and follow up on the training implementation. Accordingly, the present study aims to examine the effect of training according to the American Heart Association (AHA) and the American College of Cardiology (ACC) clinical practice guideline, with and without follow-up through telenursing on stage 1 hypertension among older adult patients with stable angina pectoris. Methods: This is quasi-experimental research conducted in 2021 with a pre-test and post-test design and a control group. The study subjects were 59 patients with stage I hypertension suffering from stable angina pectoris who were referred to Ahmadieh Heart Clinic affiliated with Torbat Heydarieh University of Medical Sciences, Torbat Heydarieh City, Iran. The participants were recruited by targeted sampling and were assigned into intervention (n=30) and control (n=29) groups using the balanced block randomization. Both groups underwent lifestyle modification training based on ACC/AHA clinical practice guideline. In the experimental group, follow-up was done through telenursing once a week for three months, and the control group followed the clinic's standard services. The data were gathered using a demographic set of questions and an aneroid sphygmomanometer. The obtained data were analyzed using the t-test, chi-square test, Mann-Whitney test, Wilcoxon test, and Fisher exact test in SPSS software, version 20. The significance level was set at P<0.05. Results: Compared to before the intervention, systolic blood pressure (P=0.009) and diastolic blood pressure (P=0.019) of the experimental group decreased significantly after the intervention. However, no significant difference was seen in the average pulse pressure (P=0.125) of the intervention group after the intervention. After the intervention, the systolic (P=0.001) and diastolic (P=0.002) blood pressure, as well as pulse pressure (P=0.006) of the intervention group, decreased significantly compared to the control group. Conclusion: Telenursing is suggested as an efficient method of controlling and managing hypertension in older adults with stable angina pectoris.